Hukum dan Ketertiban Lalu Lintas: Perspektif Sosiologi Hukum pada Undang-Undang Nomor 22 Tahun 2009 - Muntaha, Muhamad Guntur; Permana, Fadhil Azhar; Firmansyah, Rizki; Harahap, Chisa Belinda (UIN Sunan Gunung Djati Bandung, 2025)
This study aims to analyze the implementation of Law No. 22/2009 on Road Traffic and Transportation (LLAJ Law) in Bandung City, particularly related to the low public awareness in complying with traffic rules and the effectiveness of law enforcement. The background of the problem raised is the low public compliance with traffic rules, which triggers traffic violations and accidents. This research uses a qualitative approach with a literature study method to explore data from various relevant sources, including books, journals, and laws and regulations. The collected data were analyzed through three stages, namely organizing, synthesizing, and identifying key issues related to the implementation of the LLAJ Law. The research findings show that although the LLAJ Law has a clear objective to create traffic order, its implementation in Bandung City is constrained by low public legal awareness and unreliable law enforcement. Therefore, social control in traffic needs to be strengthened through increased surveillance, public education, and more consistent law enforcement. This study suggests the need for a strategic approach involving the use of technology, increasing the number of officers, and social campaigns based on the cultural context of the community to create an orderly and safe traffic culture.